Antibiotic susceptibility pattern of organisms causing surgical site infection - Lakshmi, Saranya K.; Gowda, Hema Narasimhe; K., Anuradha (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Approximately 30-50% of antibiotic use in hospitals is now for pre-surgical prophylaxis. Selection of antibiotics for prophylaxis should be based on its activity against expected bacteria at the desired surgical site. Appropriate antibiotic prophylaxis can reduce the risk of postoperative morbidity and mortality. Abuse of antimicrobials increases the cost of treatment and supports the emergence of resistant bacteria. This study was undertaken with the primary objective of to test the antibiotic susceptibility pattern of organisms causing SSIs. Methods: A descriptive study was carried out in general surgical wards of KR hospital, Mysore for a period of 18 months (2015-2016). The relevant data was collected from the case sheets of patients who were diagnosed with SSI. Pus samples were collected, and culture-sensitivity was done. Collected data were analysed using appropriate statistical tests. Results: A total of 263 study subjects including both males and females were enrolled in the study. Out of 263 pus samples 92% were culture positive. The most common organisms causing SSI were E. Coli-ESBL (n=73) and MRSA (n=44). Gram-negative organisms were highly resistant to β-lactam antibiotics and Gram-positive organisms were resistant to cotrimoxazole, erythromycin, clindamycin, cefoxitin and ciprofloxacin. Conclusions: Good hygienic measures should be followed by the patients and health-workers. A revision of hospital antibiotic policy according to the local antibiotic susceptibility pattern is recommended.